2013
DOI: 10.2494/photopolymer.26.309
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Printing of Au Micropatterns on Polyimide Films

Abstract: The transfer printing of Au micropatterns onto a polyimide (PI) film was investigated, and the optimum transfer conditions were obtained. In this study, micropatterns with widths of 25 μm and 75 μm were successfully transferred onto a PI film at a molding temperature of 150 °C for 5 s under a molding pressure of 2.5 MPa. This technique is expected to provide simplified processes in fabricating wiring patterns in microelectromechanical systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…With the development of conductive inks and the improvement in the printing resolution of inkjet printers, it is possible to print wiring with Ag ink [22] or Au ink. [23,24] Additionally, a method of transferring printed wiring between two substrates [25,26] has been devised. We recently reported that a poly(D, L-lactic acid) (PDLLA) nanosheet (thickness: 182 nm) can be employed as a base material of a wirelessly powered device.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of conductive inks and the improvement in the printing resolution of inkjet printers, it is possible to print wiring with Ag ink [22] or Au ink. [23,24] Additionally, a method of transferring printed wiring between two substrates [25,26] has been devised. We recently reported that a poly(D, L-lactic acid) (PDLLA) nanosheet (thickness: 182 nm) can be employed as a base material of a wirelessly powered device.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PI is expected to withstand the high temperatures required for the sterilization process. PI-based microstructures have already been shown to be transferable by hot embossing and are therefore suitable for microelectromechanical systems (MEMS) fabrication processes [18][19][20][21][22][23]. However, conventional PI is not transparent and has an opaque tan color, which would make it difficult to observe any cells cultured on PI sheets.…”
Section: Introductionmentioning
confidence: 99%